Draft genome sequences of two opportunistic pathogenic strains of Staphylococcus cohnii isolated from human patients - Mendoza Olazarán, Soraya Sarahí; García Mazcorro, José Francisco; Morfín Otero, Rayo; Villarreal Treviño, Licet; Camacho Ortiz, Adrián; Rodríguez Noriega, Eduardo; Bocanegra Ibarias, Paola; Maldonado Garza, Héctor Jesús; Dowd, Scot E.; Garza González, Elvira (2017)
Abstract Herein, we report the draft-genome sequences and annotation of two opportunistic pathogenic strains of Staphylococcus cohnii isolated from humans. One strain (SC-57) was isolated from blood from a male patient in May 2006 and the other (SC-532) from a catheter from a male patient in June 2006. Similar to other genomes of Staphylococcus species, most genes (42%) of both strains are involved in metabolism of amino acids and derivatives, carbohydrates and proteins. Eighty (4%) genes are involved in virulence, disease, and defense and both species show phenotypic low biofilm production and evidence of increased antibiotic resistance associated to biofilm production. From both isolates, a new Staphylococcal Cassette Chromosome mec was detected: mec class A, ccr type 1. This is the first report of whole genome sequences of opportunistic S. cohnii isolated from human patients. Keywords: Short genome report, Staphylococcus cohnii , Coagulase-negative staphylococci, Clinical strains, Biofilm, SCCmec